Palliative care patients' perceptions of the work involved in understanding and managing the network of care provision surrounding them. Issue 2 (31st March 2015) - Jarrett, N; Porter, K; Davis, C; Lathlean, J; Duke, S; Corner, J; Addington-Hall, J
Abstract : Objective: To explore the work carried out for cancer palliative care patients in understanding and dealing with the often large network of care provision surrounding them. Method: Qualitative thematic analysis of interviews with 24 patients (aged 48–85 years) with 15 different types/sites of cancer and palliative care needs. Results: The main theme of 'patient work—their strategies and project management' is presented. Subthemes included: being organised and keeping records; planning ahead and coordinating care; information gathering; understanding the hierarchy and knowing who the key people are; strategies to remember names and roles; understanding and 'working the system'. Insights are given into the work carried out on patients' behalf by family, although it was unclear who would do this work if no family was available. Some of the challenges faced by patients and families are identified. These included limited information; uncertainty when care is transferred between different teams or locations; deciding who to contact and how; and negotiating through gatekeepers. Conclusions: The number and variety of people contributing to the care of a cancer palliative care patient can be difficult for patients and family to comprehend. Work is required by patients or family on their behalf to achieve the level of understanding required to become accomplished at navigating the system and project managing their care organisation, and is probably influenced by role expectations and previous experience. Much of this additional, often hidden, workload for patients and family could probably be reduced with clear, timely information provision by health professionals.